Bifunctional Phase‐Transfer Catalysts Catalyzed Diastereo‐ and Enantioselective Aza‐Henry Reaction of β, γ‐Unsaturated Nitroalkenes With Amidosulfones. Issue 23 (27th September 2017) - Lu, Ning; Bai, Fuquan; Fang, Yanhong; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Lin, Yingjie; Duan, Haifeng
Abstract: An efficient diastereo‐ and enantioselective aza‐Henry reaction of β, γ ‐unsaturated nitroalkenes with N‐ Boc amidosulfones has been realized under the catalysis of bifunctional chiral phase‐transfer catalysts bearing multiple H‐bonding donors, which was derived from cinchona alkaloids. This asymmetric catalytic protocol is suitable for a wide range of substrates, and give the corresponding products in high to excellent yields (up to 99%) with excellent diastereo‐ and enantioselectivities (up to >99 : 1 dr, up to >99% ee). Density functional theory (DFT) calculations are also performed and give the possible transition‐state model to illustrate the mechanism of the developed reaction. Abstract :